Bovine skin fibroblasts mediated immune responses to defend against bovine Acinetobacter baumannii infection. (December 2022) - Hou, Simeng; Wu, Haotian; Chen, Si; Li, Xubo; Zhang, Zhenxing; Cheng, Yiwen; Chen, Yuanyuan; He, Meirong; An, Qi; Man, Churiga; Du, Li; Chen, Qiaoling; et al.
Abstract: Acinetobacter baumannii ( A. baumannii ) is an opportunistic pathogen which can cause pneumonia, sepsis and infections of skin and soft tissue. The host mostly relies on innate immune responses to defend against the infection of A. baumannii . Currently, it has been confirmed that fibroblasts involved in innate immune responses. Therefore, to explore how bovine skin fibroblasts mediated immune responses to defend against A. baumannii infection, we analyzed the differential transcripts data of bovine skin fibroblasts infected with bovine A. baumannii by RNA-sequencing (RNA-seq). We found that there were 3014 differentially expressed genes (DEGs) at 14h with bovine A. baumannii infection, including 1940 up-regulated genes and 1074 down-regulated genes. Gene Ontology (GO) enrichment showed that ubiquitin protein ligase binding, IL-6 receptor complex, ERK1 and ERK2 cascade terms were mainly enriched. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment showed that innate immune pathways were significantly enriched, such as TNF, IL-17, NLR, MAPK, NF-κB, endocytosis, apoptosis and HIF-1 signaling pathways. Furthermore, Gene Set Enrichment Analysis (GSEA) revealed that GO terms such as chemokine receptor binding and Th17 cell differentiation and KEGG pathways such as TLR and cytokine-cytokine receptor interaction pathways were up-regulated. In addition, CASP3 and JUN were the core functional genes of apoptosis, while IL-6, ERBB2, EGFR, CHUK and MAPK8 were the core functional genes of immunity by Protein-Protein Interaction (PPI) analysis. Our study provided an in-depth understanding of the molecular mechanisms of fibroblasts against A. baumannii infection. It also lays the foundation for the development of new therapeutic targets for the diseases caused by A. baumannii infection and formulates effective therapeutic strategies for the prevention and control of the diseases caused by A. baumannii . Highlights: Highly virulent A. baumannii conferred immune responses on fibroblasts at MOI = 30. A large number of DEGs involved in innate immunity such as IL-6, etc. KEGG and GSEA enrichment showed that TLR, NLR, IL-17, TNF, endocytosis, apoptosis, MAPK signaling pathways were enriched. CASP3 and JUN were the core genes of apoptosis, while IL-6, ERBB2, EGFR, CHUK and MAPK8 were the core genes of immunity.